Prolonged COVID 19 Outbreak and Psychological Response of Nurses in Italian Healthcare System: Cross-Sectional Study - Ranieri, Jessica; Guerra, Federica; Perilli, E.; Passafiume, Domenico; Maccarone, D.; Ferri, C.; Di Giacomo, Dina (Frontiers in Psychology, 2021)
Aim of the study was to analyse the posttraumatic stress disorder risk nurses, detecting the relationship between distress experience and personality dimensions in Italian COVID-19 outbreak. A cross-sectional study was conducted based on 2 data detection (March 2020 and September 2020). Mental evaluation was carried out in Laboratory of Clinical Psychology on n.69 nurses in range age 22-64 years old (mean age 37,3; sd 10,3; 55% working in nursing care with confirmed COVID-19 patients (named frontline; secondline nurses have been identified by nursing care working with infectious patients but no confirmed COVID-19). Measurement was focused on symptoms anxiety, personality traits, peritraumatic dissociation and posttraumatic stress for all participants. No online screening was applied. Comparisons (ANOVA test) within the various demographic characteristics demonstrated few significant differences between groups on DASS-21, PDEQ, and ISE-R scores. Correlation analysis (Spearman test) was performed among PDEQ, DASS-21, BFI-10 and IES-R and confirmed between anxiety (DASS-21) and peritraumatic dissociation and posttraumatic stress; then anxiety is positively correlated to agreeableness variable of BFI-10 test. The emotional distress was protracted overtime (after 6 months) but in long-term personality traits resulted mediator facing subjective stress. Our finding drew details for protective and predictive risk factors as well as mental health issues of nurses dealing with pandemic: healthcare workers faced the protracted challenge caring COVID-19 patients over and over again: in short time the impact was relevant, and the prolonged exposition to the stressor was tackled by personal resources such as personality traits.